Road Safety for Motorcycle Users among High School Students - Rahmadani, Farah Nabilla; Wahyuningsih, Anik Setyo (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Background: Safety riding aims to prevent traffic accidents. The number of traffic accidents in Wonosobo Regency, the age group most frequently involved in accidents is 16-25 years old. Accidents in the 16-25 year age group in 2021 were 34% and will increase to 43% in 2022.Methods: This research uses descriptive analytical methods with a cross sectional approach. The population in this study were students at Mojotengah Public High School 1, totaling 837 students with a sample of 271 respondents. Samples were taken from 3 classes using proportionate stratified random sampling. Data were collected using a questionnaire and data were analyzed using the Chi-Square test and multiple logistic regression.Results: Research shows that there are 3 variables that are statistically related to safety riding: knowledge, perception and driving experience.Conclusions: Knowledge, perception and driving experience are related to safety riding and can increase safe driving in students by 50.9%.